Effect of goal orientations on pre-emptive downplay. - Gooi, Ling Hoong. (2009)
This paper examines pre-emptive effort downplay (PED) in the light of the different goal orientations. It was hypothesized that individuals with mastery goal orientation would engage in lesser amounts of PED compared to those with performance goal orientations, within which individuals with performance avoid goals would be more likely to engage in PED compared to those with performance approach goals. However, such trends were not found. Instead, it was found that there were high correlations between endorsements of the three goals and generally little display of PED, and, in some cases, over-reporting of effort. This might be due to cultural beliefs that ability is changeable through effort; hence PED might not have been a helpful self-handicapping strategy to use.